Evaluation of awareness about obesity among general public visiting the tertiary care hospital - Arunachalam, Umamageswari; Nagesh, Simhadri V. S. D. N. A.; Vivekkumar, S. Priestly; V. S., Abinaya (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Obesity is one of the fastest growing threats of health and well-being for both developed and developing countries. The aim of the study was to evaluate the awareness about obesity among general public. Methods: After obtaining institutional ethics committee approval and written informed consent from the participants, anthropometric measures like height, weight, hip and waist circumference for computing body mass index and waist hip ratio were taken. Using portable bioelectric impedance analyzer body fat percentage was measured. A validated questionnaire including socio demographic details and questions evaluating the awareness about obesity were given to the participants. Results: Totally 100 participants were evaluated, of which majority being female. Mean height of the male and female participants was 164 and 152cm respectively. Similarly, mean weight was found to be 72 and 65 kg. Based on the body mass index only 19% participants were within normal range, remaining 81% were overweight and obese. Percent body fat and waist hip ratio was found to be increased in both sexes. Majority of the participants were aware that obesity is associated with health problems but most of them were unaware how it is measured and the dietary foods to be taken to reduce obesity. However 64% participants think that obesity can reduce the life expectancy of the individual. Conclusions: Majority of the participants were obese and overweight while awareness about preventive measures was still lacking. Hence health care personnel need to take greater effort to educate and inform people about the implications.